2016
DOI: 10.1111/mec.13838
|View full text |Cite
|
Sign up to set email alerts
|

Demographic modelling with whole‐genome data reveals parallel origin of similarPundamiliacichlid species after hybridization

Abstract: Modes and mechanisms of speciation are best studied in young species pairs. In older taxa, it is increasingly difficult to distinguish what happened during speciation from what happened after speciation. Lake Victoria cichlids in the genus Pundamilia encompass a complex of young species and polymorphic populations. One Pundamilia species pair, P. pundamilia and P. nyererei, is particularly well suited to study speciation because sympatric population pairs occur with different levels of phenotypic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
181
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(190 citation statements)
references
References 118 publications
(281 reference statements)
8
181
1
Order By: Relevance
“…). To test whether this was repeatable and whether parasitism correlated with crevice‐dwelling in Pundamilia , but also to test for more general repeatability of parasite trends in similar cases of species divergence, we compared infections between sympatric red/blue pairs of Pundamilia at Makobe and three other islands with phenotypically similar species or morph pairs (Seehausen et al ., ; Meier et al ., ). We found that the total parasite abundance was strongly correlated between sympatric Pundamilia spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). To test whether this was repeatable and whether parasitism correlated with crevice‐dwelling in Pundamilia , but also to test for more general repeatability of parasite trends in similar cases of species divergence, we compared infections between sympatric red/blue pairs of Pundamilia at Makobe and three other islands with phenotypically similar species or morph pairs (Seehausen et al ., ; Meier et al ., ). We found that the total parasite abundance was strongly correlated between sympatric Pundamilia spp.…”
Section: Resultsmentioning
confidence: 99%
“…‘pundamilia‐like’ and P. sp. ‘nyererei‐like’, and at Luanso, it is a single genetically panmictic population with polymorphic male colouration (Meier et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Given the presence of linked sites in our data set (i.e., mean of 2.8 and median 2 SNPs per 89 bp locus), AIC analyses could be associated with increased error and bias towards more complex models and this analysis should be interpreted with caution (Coffman et al, ). However, other studies apply AIC methods to composite likelihoods as a first approximation in ranking models (e.g., Meier et al, ; Oswald, Overcast, Mauck, Andersen, & Smith, ). In cases where the model with the highest likelihood included more parameters than hierarchically nested models with lower likelihood values, we performed a likelihood ratio test with a GIM‐based adjustment to account for the use of composite likelihoods (Coffman et al, ).…”
Section: Methodsmentioning
confidence: 99%